Multiple drivers of large‐scale lichen decline in boreal forest canopies. (8th March 2022) - Esseen, Per‐Anders; Ekström, Magnus; Grafström, Anton; Jonsson, Bengt Gunnar; Palmqvist, Kristin; Westerlund, Bertil; Ståhl, Göran
Abstract: Thin, hair‐like lichens ( Alectoria, Bryoria, Usnea ) form conspicuous epiphyte communities across the boreal biome. These poikilohydric organisms provide important ecosystem functions and are useful indicators of global change. We analyse how environmental drivers influence changes in occurrence and length of these lichens on Norway spruce ( Picea abies ) over 10 years in managed forests in Sweden using data from >6000 trees. Alectoria and Usnea showed strong declines in southern‐central regions, whereas Bryoria declined in northern regions. Overall, relative loss rates across the country ranged from 1.7% per year in Alectoria to 0.5% in Bryoria . These losses contrasted with increased length of Bryoria and Usnea in some regions. Occurrence trajectories (extinction, colonization, presence, absence) on remeasured trees correlated best with temperature, rain, nitrogen deposition, and stand age in multinomial logistic regression models. Our analysis strongly suggests that industrial forestry, in combination with nitrogen, is the main driver of lichen declines. Logging of forests with long continuity of tree cover, short rotation cycles, substrate limitation and low light in dense forests are harmful for lichens. Nitrogen deposition has decreased but is apparently still sufficiently high to prevent recovery. Warming correlated with occurrence trajectories of Alectoria and Bryoria, likely by altering hydration regimes and increasing respiration during autumn/winter. The large‐scale lichen decline on an important host has cascading effects on biodiversity and function of boreal forest canopies. Forest management must apply a broad spectrum of methods, including uneven‐aged continuous cover forestry and retention of large patches, to secure the ecosystem functions of these important canopy components under future climates. Our findings highlight interactions among drivers of lichen decline (forestry, nitrogen, climate), functional traits (dispersal, lichen colour, sensitivity to nitrogen, water storage), and population processes (extinction/colonization). Abstract : Thin, hair‐like lichens have important ecosystem functions in boreal forest canopies. We analyse how environmental drivers influence changes in occurrence and length of these lichens in the lower canopy of Norway spruce ( Picea abies ) over 10 years in managed forests in Sweden using data from >6000 trees in the National Forest Inventory. Alectoria and Usnea showed strong declines in southern‐central regions, whereas Bryoria declined in northern regions. Our analysis strongly suggests that the decline was mainly driven by industrial forestry, in combination with nitrogen deposition. Our study highlights interactions among drivers of lichen decline, functional traits and population processes.